Assurance of Learning and Assessment at the Business Degree Program and Major Levels - Zhu, Faye X.; Fleming, Robert S. (Archives of Business Research, 2017)
This study presents one business school’s experiences in simultaneously undergoing the accreditation processes of both the Association to Advance Collegiate Schools of Business International (AACSB) and the Middle States Commission on Higher Education (MSCHE). AACSB International is a worldwide accreditor of business schools, while MSCHE is a regional accreditor of colleges and universities in the Middle States region of the United States and several other locations internationally. It discusses the process of assurance of learning (AOL) and assessment at the degree program level for the business school’s AACSB accreditation and at the major level for the institution’s MSCHE accreditation.